A Newborn Midwifery Care Management for Mrs. â€œRâ€ with Mild Asphyxia at the UPT Ulaweng Health Center BLUD: Manajemen Asuhan Kebidanan Bayi Baru Lahir Pada Bayi Ny â€œRâ€ Dengan Asfiksia Ringan Di BLUD UPT Puskesmas Ulaweng - Ita Novianti; Syahririn Syahririn; Asrianti Safitri Muchtar (Jurnal Midwifery, 2023)
Introduction Asphyxia is a condition in newborns in which there is regular spontaneous respiratory failure immediately after birth. WHO states that birth asphyxia is the 3rd leading cause of infant death in the world in the early period of life. Previous data showed that in 2022 there will be 12,114 newborns born in Bone Regency and 550 will experience asphyxia (4.54%). The importance of proper care and the high incidence of newborn asphyxia. The purpose of this research was to provide midwifery care for newborns with asphyxia in infants at the BLUD UPT Ulaweng Health Center in accordance with the needs and authority of midwives. Methods this study uses Varney's 7-step midwifery care management method and SOAP. Results Based on the case studies that have been carried out, it shows that the newborn baby Ny 'R" with mild asphyxia can be handled well. Conclusion Furthermore, the assessment, analysis, and documentation related to all actions and treatment were documented. Hence, it could be suggested that the findings of this research were in line with previous theories.